Kekerasan Simbolik Dalam Pendidikan Islam Jenjang Ibtidaiyah Di Indonesia - Hamam Fitriana (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2020)
Some textbooks still contain forms of violence. There is a type of violence that is latently perpetuated or reproduced as a habit of social and cultural structures which is called symbolic violence. In textbooks, how are forms of symbolic violence perpetuated or reproduced through language, namely in sentences and images. As a descriptive-analytic research library, the researcher tries to analyze the integrated thematic textbook 2013 curriculum for SD/MI which contains gender class distinctions between male and female classes. The distinction of gender classes in textbooks is then described and described by researchers and then analyzing sentences and images that contain symbolic violence. In the sentences in the textbook, there is a male class dominance, namely there are 62 sentences or 61.8% sentences while the female class is only 40 sentences or 39.2% sentences. In the picture, the male class dominates, namely there are 78 pictures or 65%, while the female class as the dominant class has 42 sentences or 35% pictures. The results showed that the male class dominates the female class in sentences and pictures. Male class domination is a form of socialization of the dominant class habitus to the dominated class. The socialization of the dominant class habitus is carried out in order so that the habits of social and cultural structures can be perpetuated or reproduced so that they are accepted as things that are justified and imitated. This in Pierre Bourdieu's language is said to be symbolic violence.